Istikhdam Thoriqoh Ta'lim an-Nahwi 'ala Asasi Rasmi Khoritoh al-Mafhum lada Tholabah al-Madrasah ad-Diniyah "Al-Amin" Kepanjen Malang - ilma (AL-WIJDÃN Journal of Islamic Education Studies, 2019)
The educational methods constitute an essential element in teaching the Arabic language and its grammar. The educational methods for teaching grammar were boring. The teacher must choose the appropriate educational method with enough students and the existing school tools. Most of the grammar books for students of the religious school are still in the form of paragraph descriptions only. This made the book boring and difficult to understand. Therefore, the teacher needs an educational method of grammar based on the new and interesting look. One of the interesting new forms suitable for grammar is the educational book in the form of a mind map. The entry used in this research is the quantitative entry and the researcher used the experimental method in this research. The use of the Concept Map method made the grammar process effective. The researcher has also resolved the data related to the aforementioned code. It has also been reported in the data analysis table that the value of the t-test 2,019 is greater than the t-table with a 0.05 a which is 1.684, so Ho is rejected and Ha is accepted. Then it can be concluded that the students ’scores on the post-test increase more compared to the results of the pre-test. Results of observations and interviews indicate that students enjoy learning grammar using the concept maps method. Keywords: Mindmap method, grammar, Arabic language.